Application of 18F-FDG PET-CT Images Based Radiomics in Identifying Vertebral Multiple Myeloma and Bone Metastases - Jin, Zhicheng; Wang, Yongqing; Wang, Yizhen; Mao, Yangting; Zhang, Fang; Yu, Jing (Frontiers in Medicine, 2022)
Purpose: The purpose of this study was to explore the application of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) image radiomics in the identification of spine multiple myeloma and bone metastasis, and whether this method could improve the classification diagnosis performance compared with traditional methods. Methods: This retrospective study collected total of 184 lesions from 131 patients between January 2017 and January 2021. All images were visually evaluated independently by two physicians with 20 years of experience through double-blind method, while the maximum of standardized uptake value(SUVmax) of each lesion was recorded. 279 radiomics features were extracted from the region of interest(ROI) of CT and PET images of each lesion separately by manual method. After the reliability test, least absolute shrinkage and selection operator(LASSO) regression and ten-fold cross-validation were used to perform dimensionality reduction and screening of features. Two classification models of CT and PET were derived from CT images and PET images respectively and constructed by multivariate logistic regression algorithm. In addition, the ComModel was constructed by combining the PET model as well as the conventional parameter SUVmax. The performance of the three classification diagnostic models, as well as the human experts and SUVmax, were evaluated and compared, respectively. Results: A total of 8 and 10 features were selected from CT and PET images for the construction of radiomics models, respectively. Satisfactory performance of the three radiomics models were achieved in both the training and the validation groups(Training: AUC: CT: 0.909, PET: 0.949, ComModel: 0.973; Validation: AUC: CT: 0.897, PET: 0.929, ComModel: 0.948). Moreover, the PET model and ComModel showed significant improvement in diagnostic performance between the two groups compared to the human expert(Training: P=0.01 and P=0.001; Validation: P=0.018 and P=0.033), and no statistical difference was observed between CT model and human experts(P=0.187 and P=0.229, respectively). Conclusion: The radiomics model constructed based on 18F-FDG PET/CT images achieved satisfactory diagnostic performance for the classification of multiple myeloma and bone metastases. In addition, the radiomics model showed significant improvement in diagnostic performance compared to human experts and PET conventional parameter SUVmax.